2012
DOI: 10.1001/archgenpsychiatry.2011.1552
|View full text |Cite
|
Sign up to set email alerts
|

Altered Neural Reward Representations in Pathological Gamblers Revealed by Delay and Probability Discounting

Abstract: The results extend previous reports of a generally hypoactive reward system in pathological gamblers by showing that, even when subjective reward valuation is accounted for, gamblers still show altered reward representations. Furthermore, results point toward a gradual degradation of mesolimbic reward representations for delayed rewards during the course of pathological gambling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
163
8
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(194 citation statements)
references
References 69 publications
(122 reference statements)
16
163
8
1
Order By: Relevance
“…The association between the inability to tolerate delay and gambling severity, in contrast with past studies (Madden et al, 2009;Miedl et al, 2012;Petry, 2001a;Petry, 2012;Wilde, Goudriaan, Sabbe, Hulstijn, & Dom, 2013) confirms the pattern observed in Alessi and Petry's study (2003). Even if this study does not permit a comprehensive insight into the nature of this relationship, recent research on problem and non-problem gambling adolescents highlights that delay discounting is one of the strongest predictor of gambling problems (Cosenza & Nigro, 2015).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The association between the inability to tolerate delay and gambling severity, in contrast with past studies (Madden et al, 2009;Miedl et al, 2012;Petry, 2001a;Petry, 2012;Wilde, Goudriaan, Sabbe, Hulstijn, & Dom, 2013) confirms the pattern observed in Alessi and Petry's study (2003). Even if this study does not permit a comprehensive insight into the nature of this relationship, recent research on problem and non-problem gambling adolescents highlights that delay discounting is one of the strongest predictor of gambling problems (Cosenza & Nigro, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…Similarly to previous studies (Alessi & Petry, 2003;Dixon, Marley & Jacobs, 2003;Miedl et al, 2012;Kraplin et al, 2014), the steeper discounting rates found in pathological gamblers, compared to controls, indicated that people with a pathological involvement in gambling prefer immediate rewards, even if smaller, than delayed ones, showing the inability to tolerate delay in gratification.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Functional imaging studies of pathological gambling have focused largely on abnormalities in appetitive processing, reinforcement learning, and executive functions (14)(15)(16)(17). These studies identify dysregulation across an extended brain network (sometimes termed the brain reward system) that includes the ventromedial prefrontal cortex (vmPFC), striatum, amygdala, and insula.…”
mentioning
confidence: 99%